Analisis Normatif Partisipasi Politik Pemuda muslim dalam Demokrasi Digital perspektif fikih siyasah: A Normative Analysis of Muslim Youth Political Participation in Digital Democracy from the Perspective of Fiqh Siyasah - Salpiyah; Nurfadillah Wilmayanti; Hilda Hinaya; Kurniati (QISTHOSIA : Jurnal Syariah dan Hukum, 2025)
This study examines Muslim youth political participation in digital democracy from the perspective of fiqh siyasah. Using a qualitative approach with library research, the study analyzes classical and contemporary Islamic political jurisprudence alongside scholarly works on digital politics. Data were analyzed descriptively through the framework of Maqashid Sharia. The findings reveal two primary forms of digital political participation: low-cost and high-cost participation. Low-cost participation, such as liking, sharing, and commenting, is inclusive but vulnerable to misinformation and disinformation. In contrast, high-cost participation—including content creation, digital advocacy, and mobilization—demonstrates stronger commitment but risks intensifying digital polarization. To address these challenges, this study proposes a Digital Fiqh Siyasah framework grounded in four core principles: ‘Adl (justice), Amanah (responsibility), Maslahah (public interest), and Syura (deliberation). This framework serves as an ethical guide for Muslim youth citizenship in digital spaces and bridges classical Islamic political ethics with contemporary digital democratic practices.